RESTITUSI SEBAGAI PERLINDUNGAN HUKUM BAGI KORBAN INVESTASI ILEGAL PADA PLATFORM APLIKASI INVESTASI ILEGAL - Kirana Najma Salsah (2023)
The increasing public interest in investment has greatly affected economic growth in Indonesia. This does not rule out the possibility of the emergence of illegal investment applications in the midst of social life. The presence of illegal investment applications is certainly very detrimental to the society. Through this writing, the author hopes that the society will better understand the practice of default in the case of illegal investment applications. This type of research uses normative legal research sourced from primary legal materials in the form of laws and regulations as positive law in Indonesia and official documents containing legal provisions, as well as secondary legal materials in the form of books, articles, legal journals, and the internet. The tertiary legal materials used are sourced from the Kamus Besar Bahasa Indonesia (KBBI). The results of this study, the act of default is carried out directly by the illegal investment application that uses a trading robot system. Restitution can be submitted by victims or through LPSK to obtain their rights as one of the legal protections in the form of repression, while for preventive legal protection can only be done by the society by increasing digital literacy.